2022
DOI: 10.3390/nu14051106
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors, Depressive Symptoms and Lifestyle in University Students in Poland

Abstract: Young adulthood is the period from the late teens through the twenties and is associated with life transitions that could contribute to the development of obesity. Targeting this group will be critical to reversing the obesity epidemic. The aim of the study was to investigate the eating behaviors and lifestyle of healthcare students in Poland. We enrolled 227 students in the study. Convenience sampling was employed. Diet (Food Frequency Questionnaire), physical activity (International Physical Activity Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 92 publications
(122 reference statements)
2
17
0
2
Order By: Relevance
“…For example, it can be extended to participants in other countries, as long as they are also higher education students, given they particularities differentiating from other target groups, like general young adults. Many studies confirmed the singularities of the higher education students in what concerns food literacy and eating behaviors in different countries: Bangladesh [ 67 ], Belgium [ 68 ], China [ 69 ], Croatia [ 70 ], Egypt [ 70 ], Greece [ 70 ], Hungary [ 71 ], Italy [ 70 ], Jordan [ 72 ], Korea [ 73 ], Poland [ 74 ], Portugal [ 70 , 75 ], Serbia, [ 76 ], Slovenia [ 70 ], Spain [ 56 , 77 ], Syria [ 78 ], and the United States [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it can be extended to participants in other countries, as long as they are also higher education students, given they particularities differentiating from other target groups, like general young adults. Many studies confirmed the singularities of the higher education students in what concerns food literacy and eating behaviors in different countries: Bangladesh [ 67 ], Belgium [ 68 ], China [ 69 ], Croatia [ 70 ], Egypt [ 70 ], Greece [ 70 ], Hungary [ 71 ], Italy [ 70 ], Jordan [ 72 ], Korea [ 73 ], Poland [ 74 ], Portugal [ 70 , 75 ], Serbia, [ 76 ], Slovenia [ 70 ], Spain [ 56 , 77 ], Syria [ 78 ], and the United States [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the studies of the correlation between exposure to stress and biological substances in saliva, there is still a deficit of information about the interaction of biological markers with the presence of stress and depression. According to the results of the Polish study from 2022, every third student had depressive symptoms [23]. The high risk of mood disorders in this population is the result of many factors: more responsibilities, a new environment, a large amount of learning, exams, and lifestyle changes caused by self-empowerment [23].…”
Section: Discussion Clinical Implicationsmentioning
confidence: 99%
“…According to the results of the Polish study from 2022, every third student had depressive symptoms [23]. The high risk of mood disorders in this population is the result of many factors: more responsibilities, a new environment, a large amount of learning, exams, and lifestyle changes caused by self-empowerment [23].…”
Section: Discussion Clinical Implicationsmentioning
confidence: 99%
“…Personal lifestyle and dietary behaviors among medical students have already been studied in some countries to date. It has been shown that students often do not conform to national dietary guideline recommendations [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. It has been demonstrated that a course on preventive medicine and nutritional medicine can lead to improvements in individual dietary habits [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%